Water Quality Monitoring Of Golden Arowana (Scleropages Formosus) At Ornamental Aquaculture Farm, Bukit Merah, Perak - Awalluddin, Nur Atiqah Ahmad (2013)
Water quality monitoring for Arowana is to investigate the required water quality that is suitable for the fish and hence encourage its breeding. The purpose is solely to preserve this Malaysian heritage species since Bukit Merah is the only place where Golden Arowana was found to be successfully bred. A number of 14 sampling points were selected in series from upstream at Bukit Merah reservoir and end up downstream at Sungai Kurau. There are eight parameters involved which is temperature, conductivity, dissolved oxygen (DO), pH, ammoniacal nitrogen (NH3- N), suspended solids (SS), chemical oxygen demand (COD) and biochemical oxygen demand (BOD5). The monitored results were compared with the guidelines given by Department of Fisheries (DOF) and Interim National Water Quality Standard (INWQS) Class II. Result shows that the average for all sampling points were within the required guidelines except for SS. The WQI for all sampling points at Bukit Merah were classified as Class II. This signifies that WQI Class II is suitable for Arowana production where a total of 346 of Arowana fish had been produced during the monitoring period. Further, it indicates that water quality at Bukit Merah was not polluted and the water quality from upstream (water source) towards the downstream (water release) does not have a deteriorations effect due to the aquaculture activities.